Myocardial Inflammation and Dysfunction in COVID-19–Associated Myocardial Injury. (January 2021) - Weckbach, Ludwig T.; Curta, Adrian; Bieber, Stephanie; Kraechan, Angelina; Brado, Johannes; Hellmuth, Johannes C.; Muenchhoff, Maximilian; Scherer, Clemens; Schroeder, Ines; Irlbeck, Michael; Maurus, Stefan; Ricke, Jens; et al.
Abstract : Background: Myocardial injury, defined by elevated troponin levels, is associated with adverse outcome in patients with coronavirus disease 2019 (COVID-19). The frequency of cardiac injury remains highly uncertain and confounded in current publications; myocarditis is one of several mechanisms that have been proposed. Methods: We prospectively assessed patients with myocardial injury hospitalized for COVID-19 using transthoracic echocardiography, cardiac magnetic resonance imaging, and endomyocardial biopsy. Results: Eighteen patients with COVID-19 and myocardial injury were included in this study. Echocardiography revealed normal to mildly reduced left ventricular ejection fraction of 52.5% (46.5%–60.5%) but moderately to severely reduced left ventricular global longitudinal strain of −11.2% (−7.6% to −15.1%). Cardiac magnetic resonance showed any myocardial tissue injury defined by elevated T1, extracellular volume, or late gadolinium enhancement with a nonischemic pattern in 16 patients (83.3%). Seven patients (38.9%) demonstrated myocardial edema in addition to tissue injury fulfilling the Lake-Louise criteria for myocarditis. Combining cardiac magnetic resonance with speckle tracking echocardiography demonstrated functional or morphological cardiac changes in 100% of investigated patients. Endomyocardial biopsy was conducted in 5 patients and revealed enhanced macrophage numbers in all 5 patients in addition to lymphocytic myocarditis in 1 patient. SARS-CoV-2 RNA was not detected in any biopsy by quantitative real-time polymerase chain reaction. Finally, follow-up measurements of left ventricular global longitudinal strain revealed significant improvement after a median of 52.0 days (−11.2% [−9.2% to −14.7%] versus −15.6% [−12.5% to −19.6%] at follow-up; P =0.041). Conclusions: In this small cohort of COVID-19 patients with elevated troponin levels, myocardial injury was evidenced by reduced echocardiographic left ventricular strain, myocarditis patterns on cardiac magnetic resonance, and enhanced macrophage numbers but not predominantly lymphocytic myocarditis in endomyocardial biopsies. Abstract : Supplemental Digital Content is available in the text.